Mechanochromic Luminescence of Copper Iodide Clusters. Issue 15 (5th March 2015) - Benito, Quentin; Maurin, Isabelle; Cheisson, Thibaut; Nocton, Gregory; Fargues, Alexandre; Garcia, Alain; Martineau, Charlotte; Gacoin, Thierry; Boilot, Jean‐Pierre; Perruchas, Sandrine
Abstract Luminescent mechanochromic materials are particularly appealing for the development of stimuli‐responsive materials. Establishing the mechanism responsible for the mechanochromism is always an issue owing to the difficulty in characterizing the ground phase. Herein, the study of real crystalline polymorphs of a mechanochromic and thermochromic luminescent copper iodide cluster permits us to clearly establish the mechanism involved. The local disruption of the crystal packing induces changes in the cluster geometry and in particular the modification of the cuprophilic interactions, which consequently modify the emissive states. This study constitutes a step further toward the understanding of the mechanism involved in the mechanochromic luminescent properties of multimetallic coordination complexes.